The Effectiveness of Social Media Facebook IAIN Parepare in Providing Information to Prospective New Students at Sman 3 Parepare - Juswanda Safitri; Era Fasira; Muh. Ayub; Dafid Dafid; Andi Dian Fitriana; Nahrul Hayat (State Islamic Institute of Bone, Indonesia, 2022)
Social media is online media that makes it easy for audiences to provide and get information, now social media has many platforms such as Facebook. Facebook has many users who can update daily and others. The purpose of this study was to determine the effectiveness of IAIN Parepare's Facebook social media in providing information to prospective new students at SMAN 3 Parepare by covering three indicators namely frequency or intensity, duration, and activity. The method used in this research is descriptive quantitative research instrument in the form of a questionnaire given to 55 research samples (respondents) 3rd grade students of SMAN 3 Parepare. The results of this study indicate the ineffectiveness of IAIN Parepare's Facebook social media in providing information for several reasons, one of which is not using Facebook to find information regarding prospective new students. It can be concluded in this study that IAIN Parepare Facebook is not effective in providing information to prospective new students at SMAN 3 Parepare.